Structure, function, and evolution of adenovirus-associated RNA: a phylogenetic approach. - Ma, Y (1996)
To explore the structure and function of a small regulatory RNA, we examined the virus-associated (VA) RNA species of all 47 known human adenovirus serotypes and of one simian virus, SA7. The VA RNA gene regions of 43 human adenoviruses were amplified and sequenced, and the structures of 10 representative VA RNAs were probed by nuclease sensitivity analysis. Most human viruses have two VA RNA species, VA RNA, and VA RNAII, but nine viruses (19%) have a single VA RNA gene. Sequence alignments classified the RNAs into eight families, corresponding broadly to the known virus groups, and three superfamilies. One superfamily contains the single VA RNAs of groups A and F and the VA RNAI species of group C; the second contains the VA RNAI species of groups B1, D, and E and the unclassified viruses (adenovirus types 42 to 47), as well as the single VA RNAs of group B2; and the third contains all VA RNAII species. Fourteen regions of homology occur throughout the molecule. The longest of these correspond to transcription signals; most of the others participate in RNA secondary structure. The previously identified tetranucleotide pair, GGGU:ACCC, is nearly invariant, diverging slightly (to GGGU:ACCU) only in the two group F viruses and forming a stem in the central domain that is critical for VA RNA structure and function. Secondary structure models which accommodate the nuclease sensitivity data and sequence variations within each family were generated. The major structural features-the terminal stem, apical stem-loop, and central domain-are conserved in all VA RNAs, but differences exist in the apical stem and central domains, especially of the VA RNAII species. Sequence analysis suggests that an ancestral VA RNA gene underwent duplication during the evolution of viruses containing two VA RNA genes. Although the VA RNAII gene seems to have been lost or inactivated by secondary deletion events in some viruses, the high degree of homology among the VA RNAII species implies that this RNA may play an undiscovered role in virus survival. We speculate that the VA RNA genes originated from cellular sequences containing multiple tRNA genes.